Ｒesearch on Taylor Vortex’s Flow and Heat Transfer Characteristics of the Air Gap of the Motor - HAN Jia-de; ZHAO Bo-min; LU Yi-ping (Journal of Harbin University of Science and Technology)
Taylor Couette flow will produce in the air gap which lies between the stator and the rotor when the asynchronous motor applying axial ventilation system runs. This secondary flow will have a significant impact on flow and heat transfer conditions of the air gap. Three kinds of simplified air gap models are created including the smooth air gap model，the air gap model with grooves in the stator side and the air gap model with grooves in the rotor side according to the structure size of the air gap for some asynchronous motor. Based on Computational Fluid Dynamics Principle and Finite Volume Method，vortex’s flow and heat-transfer characteristic in the air gap is numerically simulated by using Fluent software. The results show that the flow field is divided into two parts because of the existence of the grooves in both the stator and rotor side. The velocity of the fluid in the grooves is low relatively and flow field distribution of the mainstream area is similar to that in the smooth air gap model. On the whole，the existence of the grooves makes the Nusselt number bigger and enhances the heat transfer. Compared with the experimental correlations of the same type，the calculation error of numerical simulation of Taylor vortex’ s average Nusselt number is 7. 3% . The conclusions have reference value for the design of structure and cooling system of motor.